2021
DOI: 10.3390/biology10050383
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Retinal Degeneration in an Oxidative Stress Organ Culture Model through an iNOS-Inhibitor

Abstract: In retinal organ cultures, H2O2 can be used to simulate oxidative stress, which plays a role in the development of several retinal diseases including glaucoma. We investigated whether processes underlying oxidative stress can be prevented in retinal organ cultures by an inducible nitric oxide synthase (iNOS)-inhibitor. To this end, porcine retinal explants were cultivated for four and eight days. Oxidative stress was induced via 300 µM H2O2 on day one for three hours. Treatment with the iNOS-inhibitor 1400 W w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In total, for each staining, six cross-sections per retina were analyzed. We used n = 8/group/point in time for (immuno-) histological staining [ 39 ]. Retinas were stained with hematoxylin and eosin (H and E) using established protocols to measure the thickness of retinal layers via ZEN 2012-imaging-software (blue edition, ZEISS, Oberkochen, Germany) [ 8 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…In total, for each staining, six cross-sections per retina were analyzed. We used n = 8/group/point in time for (immuno-) histological staining [ 39 ]. Retinas were stained with hematoxylin and eosin (H and E) using established protocols to measure the thickness of retinal layers via ZEN 2012-imaging-software (blue edition, ZEISS, Oberkochen, Germany) [ 8 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…This supports the assumption that our co-cultivation model provides an option to achieve a preservation of the delicate photoreceptor cells in vitro. Under pathological conditions, iNOS was produced and caused a more severe pathophysiological response aiming in retinal degeneration [ 60 , 61 , 62 ]. In the current study, we did not detect any alteration in the amount of iNOS + and iNOS + + Iba1 + cells in the neuroretina and distinct layers in the co-culture and conditioned medium samples compared to the control ones.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we did not detect any alteration in the amount of iNOS + and iNOS + + Iba1 + cells in the neuroretina and distinct layers in the co-culture and conditioned medium samples compared to the control ones. Mueller-Buehl et al demonstrated a better preservation of porcine retina samples in an organotypic oxidative stress model by adding an iNOS-inhibitor [ 62 ]. The lacking induction of iNOS and microglial activation might indicate homeostasis of the neuroretina in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide can also be beneficial or detrimental depending on concentration. While low levels of NO are necessary for signaling, higher concentrations can be harmful to neurons (Singh et al, 2019;Mueller-Buehl et al, 2021). In the retina, small concentrations of NO are utilized for light adaptation, visual processing, and amplification of visual responses in various retinal cell types (Vielma et al, 2012;Mueller-Buehl et al, 2021).…”
Section: The Role Of Ros In the Healthy Brain And Retinamentioning
confidence: 99%